Changes in Cultural Assimilation in Harmonization of Children's Social Relations - Syafrizal Syafrizal; Anwar Soleh Purba; Corry Corry (Randwick International of Social Science Journal, 2022)
This article tried to explain that the phenomenon of Chinese Indonesians in the eyes of Native Indonesians had received such diverse perceptions, it often seemed tendentious. However, in recent years, the view was disappeared due to a change in the term of designation stipulated in state legislation by no longer using the term Chinese, but Indonesian people of Chinese descent. The main problem of this study was how the shifting of cultural assimilation patterns had an impact on the harmonization of social relations between Chinese Indonesians and Native Indonesians in Pekanbaru City, Riau Province (viewed from a social anthropological perspective). This study was conducted using a quantitative approach with field data collection instruments using a questionnaire technique for selected informants. The results of data analysis showed that there had been a shift in the assimilation pattern of Chinese Indonesians so that it had an impact on the harmonization of social relations in the community of Pekanbaru City, Riau Province.